Ionization Potential Depression in Hot Dense Plasmas Through a Pure Classical Model. Issue 5 (1st April 2015) - Calisti, A.; Ferri, S.; Talin, B.
Abstract The ionization potential of an ion embedded in a plasma, lowered due to the whole of the charged particles (ions and electrons) interacting with this ion, is the so‐called plasma effect. A numerical plasma model based on classical molecular dynamics has been developed recently. It is capable to describe a neutral plasma at equilibrium involving ions of various charge states of the same atom together with electrons. This code is used here to investigate the ionization potential depression (IPD). The study of the IPD is illustrated and discussed for aluminum plasmas at mid and solid density and electron temperatures varying from 50eV to 190eV. The method relies on a sampling of the total potential energy of the electron located at an ion being ionized. The potential energy of such electron results from all of the interacting charged particles interacting with it. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)